Analysis and evaluation of the effectiveness of government programs and projects in the Republic of Kazakhstan - Yessengeldin, B.S.; Katyshev , D.M. (BUKETOV BUSINESS REVIEW, 2017)
The article discusses the need for evaluation of public programs and projects. The article defines the number of state programs of the Republic of Kazakhstan for 2010-2016 years, aimed at implementing the priorities of the strategic development of the country. The authors note that the number of government programs varies each year depending on the state vision of the country's development prospects. The authors analyzed the 8 existing state programs that establish clear national priorities in the areas of education, health, language development and industrialization. The paper evaluated the effectiveness of the state program for accelerated industrial-innovative development of Kazakhstan for 2010-2014, based on the Ministry of National Economy and the Accounts Committee for Control over Execution of the Republican Budget. The authors considered the Republican Industrialization Map projects in the context of the Republic of Kazakhstan regions. The article revealed that the projects of republican value in 2010-2014 have been implemented in the main city of Astana, Zhambyl, Karaganda, Pavlodar and Mangistau regions. The article also identifies that the years 2015- 2019 the largest number of projects planned in Pavlodar and Atyrau regions. The authors identified the main problems hampering quality and efficient development and implementation of government programs and projects.